2016
DOI: 10.2320/matertrans.m2016341
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Collagen Matrix Alignment in Osteolytic Bone Metastasis Induced by Breast Cancer

Abstract: Breast cancer is highly metastatic to bone tissue and causes osteolytic lesions through osteoclast activation. Although the effects of osteolytic metastasis on bone quantity have been well studied, whether osteoclast activation induced by cancer bone metastasis affects the bone microstructure, a notable aspect of the bone quality, remains uncertain. The aim of this study was to clarify the effect of osteolytic bone metastasis in breast cancer on the microstructure of the bone matrix, particularly the integrity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…We have clarified that apatite orientation is the dominant determiner of bony mechanical function [ 19 ]. The ex vivo tumor-invaded bone showed a significantly disrupted alignment of apatite crystals ( Figure 2 ), which is consistent with our previous in vivo reports [ 7 , 8 , 20 ]. Our ex vivo model can represent the alteration of bone apatite orientation in response to the external loading conditions [ 21 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We have clarified that apatite orientation is the dominant determiner of bony mechanical function [ 19 ]. The ex vivo tumor-invaded bone showed a significantly disrupted alignment of apatite crystals ( Figure 2 ), which is consistent with our previous in vivo reports [ 7 , 8 , 20 ]. Our ex vivo model can represent the alteration of bone apatite orientation in response to the external loading conditions [ 21 ].…”
Section: Discussionsupporting
confidence: 92%
“…Intact bone tissue exhibits a characteristic anisotropic microstructure based on collagen fiber alignment and the related c -axis orientation of apatite crystals [ 4 , 5 ], which is derived from the intercellular molecular events mediating the cellular arrangement [ 6 ]. We recently discovered that the disorganized, less-aligned collagen/apatite microstructure in cancer-bearing bone is a dominant determiner in the disruption of bone mechanical function [ 7 , 8 ]. However, the biological scenarios that stimulate the disorganization of metastasized bone microstructures are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…In bone metastatic cancers, type I collagen production and orientation is known to be altered [66,68]. There is increased collagen production at the bone metastatic site, whereby secreted collagen molecules are dense, misaligned, and disorganized, further disrupting bone mechanical function (Figure 5b) [66,75]. Liu et al identified that metastatic breast cancer cells secreted miR-218 which directly regulated type I collagen secretion from osteoblasts in the bone niche [76].…”
Section: The Bone Extracellular Matrixmentioning
confidence: 99%
“…Tumor invasion and metastasis effect dynamic changes in targeted organs both histologically and genetically 3 . Interestingly, our recent study revealed that cancer cells alter the anisotropic microstructure of metastasized bone 4 5 . Homing of cancer cells to bone induces disrupted mechanical function derived from the disorganized microstructure associated with the less aligned crystallographic structure of apatite c -axis with the hexagonal lattice of the P6 3 /m space group.…”
mentioning
confidence: 99%
“…Recently, we had established a bone-mimetic anisotropic culture model by controlling the orientation of the substrate collagen 11 . Further development of the culture model by combining the artificially-controlled anisotropic culture substrate with the cancer-bone coculture system is necessary to study the cellular mechanisms behind the metastasis-mediated disorganization of the anisotropic bone microstructure 4 5 . Here, focusing on the cellular orientation in response to the collagen molecular anisotropy, coculture of cancer cells and osteoblasts was performed on an artificially controlled oriented collagen scaffold.…”
mentioning
confidence: 99%